Computing rational powers of monomial ideals. (May 2023) - Dongre, Pratik; Drabkin, Benjamin; Lim, Josiah; Partida, Ethan; Roy, Ethan; Ruff, Dylan; Seceleanu, Alexandra; Tang, Tingting
Abstract: This paper concerns fractional powers of monomial ideals. Rational powers of a monomial ideal generalize the integral closure operation as well as recover the family of symbolic powers. They also highlight many interesting connections to the theory of convex polytopes. We provide multiple algorithms for computing the rational powers of a monomial ideal. We also introduce a mild generalization allowing real powers of monomial ideals. An important result is that given any monomial ideal I, the function taking a real number to the corresponding real power of I is a step function which is left continuous and has rational discontinuity points.